ANALISIS KRIMINOLOGIS TERKAIT HOTSPOT OF CRIME:STUDI KASUS KAWASAN RAWAN KRIMINALITAS JAKARTA TIMUR DI JATINEGARA DAN CAKUNG - Ibnu Muhammad Romzi; Alysha Fedelia; Nadya Nurluthfi Aqilah; Anggita; Syailendra Bintang Bramasta; Rofiq Arfathzil Go'o; Radja Maulana Chairurrijal (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
crime areas (hotspots) in East Jakarta, namely Cakung and Jatinegara. Employing a descriptive qualitative approach and spatial analysis, data were collected from real case reports found in online news and community accounts. The findings reveal that the high incidence of theft is driven by weak neighborhood security, limited surveillance, and low public trust in law enforcement. Offendersuse various methods, including fake keys, posing as debt collectors, and exploiting personal relationships. Community responses, often involving vigilantism, indicate a lack of confidence in the legal system. This research highlights the importance of local data-driven crime prevention strategies, such as increased patrols, CCTV installation, and community safety education to reduce crimerates in hotspot areas.